2013
DOI: 10.17221/18/2012-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of Ochratoxin A by marine bioluminescent bacteria V. harveyi BA

Abstract: Wang W., Zhang M., Fang J., Zhang L., Zou X., Wang X. (2013): Improved detection of Ochratoxin A by marine bioluminescent bacteria V. harveyi BA. Czech J. Food Sci., 31: 88-93.We applicate the bioluminescent assay system for evaluating the toxicity of Ochratoxin A (OTA). The optimum conditions for the growth and bioluminescence of V. harveyi BA were investigated, including NaCl concentration and pH in the medium, incubation temperature, and OTA action time. The growth and luminescence reached the perfect phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(18 reference statements)
1
3
0
Order By: Relevance
“…[ 27 ] These findings are consistent with the results of Wang et al. [ 28 ] who studied the reduction of solubility and swelling power of different starches by moist heat treatment.…”
Section: Resultssupporting
confidence: 90%
“…[ 27 ] These findings are consistent with the results of Wang et al. [ 28 ] who studied the reduction of solubility and swelling power of different starches by moist heat treatment.…”
Section: Resultssupporting
confidence: 90%
“…It is known that, in their suspended form, bacterial P. phosphoreum cells and several other strains can be used for determining the presence of micotoxins [25]. The spectrum of mycotoxins and the range of their concentrations that can be detected using bioluminescent bacterial cells are known from various scientific publications (Table 1) [25,26,27,28,29,30,31]. However, the possibility of using bioluminescent bacterial cells in an immobilized form for the analysis of mycotoxins has not been investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…(2006) and Wang et al . (2013) also reported that luminescence decreased when stationary phase was reached at 24 h …”
Section: Resultsmentioning
confidence: 89%